1988
DOI: 10.1002/art.1780311109
|View full text |Cite
|
Sign up to set email alerts
|

Examination of subchondral bone architecture in experimental osteoarthritis by microscopic computed axial tomography

Abstract: Subchondral bone changes have been proposed as an early event in the pathogenesis of osteoarthritis. In this study, microscopic computed axial tomography was used to evaluate the subchondral bone structure in femoral heads from a guinea pig model of osteoarthritis. Examination of trabecular bone within the femoral head showed a highly significant increase in bone fraction in the experimental animals. This was due to the development of trabeculae that were thicker and closer together. We conclude that trabecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
73
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 15 publications
12
73
1
Order By: Relevance
“…This indicates that a modification of the trabecular structure leading to bone sclerosis appears in the most affected condyle. This result confirms the findings of a previous study performed by Layton et al (4), in which femoral heads from a guinea pig model of OA showed a highly significant increase in bone volume fraction.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that a modification of the trabecular structure leading to bone sclerosis appears in the most affected condyle. This result confirms the findings of a previous study performed by Layton et al (4), in which femoral heads from a guinea pig model of OA showed a highly significant increase in bone volume fraction.…”
Section: Discussionsupporting
confidence: 93%
“…Based on mCT findings in experimental models of OA, it has been suggested that changes in articular cartilage that occur in OA are associated with changes in the adjoining subchondral and trabecular bone (218)(219)(220). In the guinea pig, Layton et al (218) observed that an initial loss of trabecular bone volume fraction, and thinning of trabeculae in early OA was followed by an increase of trabecular bone volume fraction and trabecular thickening in the advanced stages of OA.…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 99%
“…In the guinea pig, Layton et al (218) observed that an initial loss of trabecular bone volume fraction, and thinning of trabeculae in early OA was followed by an increase of trabecular bone volume fraction and trabecular thickening in the advanced stages of OA. In a canine ACL transection model of OA, Dedrick et al (220) demonstrated an increase in subchondral bone thickness, accompanied by a decrease in trabecular thickness.…”
Section: Cross-sectional and Longitudinal Observations In Oamentioning
confidence: 99%
“…In the first, sectioning of protective musculature outside the joint produced OA in guinea pigs; animals were tracked by micro-computed tomography from the time of the operation to evaluate bony trabecular and subchondral plate thickness (9). When cartilage loss started, the subchondral plate and trabeculae underneath cartilage were thin; only later in OA development did the radiographic equivalent of "eburnation" occur with thickening of both areas of bone.…”
Section: Does Bony Sclerosis Precede Cartilage Loss In Oa?mentioning
confidence: 99%